Successful Management of a Rare Case of Dystocia in a Goat due to Ventro-Lateral Abdominal Hernia of Gravid Uterus - Singh, Bhoopendra; Kumar, Rajesh; Singh, Shubhendra Vikram; Singh, Narendra (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Dystocia or difficult birth, a condition in small ruminants (sheep and goat), results in huge economic losses to  farmers either due to death of new born(s) or dam and  adversely affects dam fertility (Mcsporran, 1980). In goat,  the incidence of dystocia is low (Bhattacharyya et al.2015). Obstetrical problems in goats are similar to those in  sheep (Majeed, 1994), however, the incidence of dystocia  is considered higher in goats compared to ewes (Mehta et  al., 2002). Hernia of the gravid uterus occasionally occurs  during advanced pregnancy in ruminants usually to the  right side of the abdominal floor (Roberts, 1971), leading to  dystocia (Oehme and Prier, 1974). Ventral abdominal hernia  occurs mainly due to any trauma such as a kick, blow, horn  thrust or falling on blunt objects or automobile accidents  (Radhakrishnan et al., 1993) and rupture of prepubic tendon  (Frank, 1981; Arthur, 1989). The condition is generally  observed in pluriparous small ruminants in advanced  pregnancy with multiple fetuses, which leads to fragility of  abdominal muscles or prepubic tendon (Vijayanand et al., 2012). This paper presents successful management of a rare  case of dystocia in a goat due to ventro-lateral abdominal  hernia of gravid uterus.
Keywords: Successful Management; Dystocia; Ventro-Lateral Abdominal Hernia; Gravid Uterus